2012
DOI: 10.1161/circgenetics.111.960831
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Myosin Binding Protein-C Mutations in Families With Hypertrophic Cardiomyopathy

Abstract: Background-Small selected cohort studies suggest that mutations in the cardiac myosin binding protein-C (MYBPC3) gene cause late-onset, clinically benign hypertrophic cardiomyopathy (HCM). Pϭ0.03). In 9 families (25 individuals) with the R502W mutation, there was marked heterogeneity in age at diagnosis (5 to 80 years), pattern of hypertrophy (11 none, 9 asymmetrical, 3 concentric, 1 apical, 1 eccentric), and prognosis (premature sudden death in 2 individuals compared with survival to advanced age in 6 indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(73 citation statements)
references
References 42 publications
3
61
0
1
Order By: Relevance
“…26,[28][29][30][31] Extreme hypertrophy was absent in FG+ relatives, and there was less adverse remodeling. Identification of HCM leads to lifestyle modifications, periodic SCD risk stratification, and close clinical follow-up, with the opportunity to implant an ICD for primary prevention and timely referral for septal reduction therapy.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…26,[28][29][30][31] Extreme hypertrophy was absent in FG+ relatives, and there was less adverse remodeling. Identification of HCM leads to lifestyle modifications, periodic SCD risk stratification, and close clinical follow-up, with the opportunity to implant an ICD for primary prevention and timely referral for septal reduction therapy.…”
Section: Discussionmentioning
confidence: 94%
“…Because of the known age-related penetrance in HCM, 29 longterm follow-up of FG+/Ph− subjects is recommended. 13,20,35 The interval at which clinical evaluation should be repeated is subject to debate.…”
Section: Fg+/ph− Individualsmentioning
confidence: 99%
“…Compared with the ␤-MHC, genetic mutations in the ELC are rare but they are also associated with malignant outcomes (3,13,17,29,42). In this report we followed up on our structural observations associated with the alanine to glycine mutation occurring at residue 57 of the human ventricular ELC shown to cause hypertrophic cardiomyopathy and SCD (29).…”
Section: Discussionmentioning
confidence: 99%
“…HCM is characterized by LV hypertrophy (i.e., increased LV wall thickness [LVWT]), myocyte enlargement and disarray, and increased myocardial fibrosis, but the severity of these manifestations and associated symptoms vary among patients. Recent studies have shown more severe LV hypertrophy (8), disease progression (9,10), and adverse outcomes, including sudden cardiac death (11,12), in men than women with HCM, information that implicates a role for genetic modifiers in disease expression. Using 5′RNA-Seq, we identified 92 genes with altered 5′ start-site usage in HCM.…”
Section: Introductionmentioning
confidence: 99%